2012
DOI: 10.1111/psyp.12001
|View full text |Cite|
|
Sign up to set email alerts
|

How does noise affect amplitude and latency measurement of event‐related potentials (ERPs)? A methodological critique and simulation study

Abstract: There is considerable variability in the quantification of event-related potential (ERP) amplitudes and latencies. We examined susceptibility of ERP quantification measures to incremental increases in background noise through published ERP data and simulations. Measures included mean amplitude, adaptive mean, peak amplitude, peak latency, and centroid latency. Results indicated mean amplitude was the most robust against increases in background noise. The adaptive mean measure was more biased, but represented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
153
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(163 citation statements)
references
References 53 publications
8
153
0
2
Order By: Relevance
“…Supplementary analyses of the non-CSD (i.e., raw) data indicated that ABM participants demonstrated reductions in the ERN and CRN but not the ΔERN. Similar results were obtained for peak-to-peak analyses; however, it is important to note that peak amplitude can produce a biased measure (Luck, 2005) and is highly sensitive to noise (Clayson, Baldwin, & Larson, 2013). The CSD transform improved spatial and temporal overlap between the response-locked ERP components (e.g., the CRN and ERN) and stimulus-locked ERP components (e.g., P300), and results from these analyses indicated reductions in the ERN, CRN, and the ΔERN.…”
Section: Discussionsupporting
confidence: 67%
“…Supplementary analyses of the non-CSD (i.e., raw) data indicated that ABM participants demonstrated reductions in the ERN and CRN but not the ΔERN. Similar results were obtained for peak-to-peak analyses; however, it is important to note that peak amplitude can produce a biased measure (Luck, 2005) and is highly sensitive to noise (Clayson, Baldwin, & Larson, 2013). The CSD transform improved spatial and temporal overlap between the response-locked ERP components (e.g., the CRN and ERN) and stimulus-locked ERP components (e.g., P300), and results from these analyses indicated reductions in the ERN, CRN, and the ΔERN.…”
Section: Discussionsupporting
confidence: 67%
“…For the HTA group, ERPs contained an average of 89±3 trials for congruent trials under low WM load, 86±5 for incongruent trials under low WM load, 89±3 for congruent trials under high WM load, and 85±6 for incongruent trials under high WM load. Notably, noise estimates were found to be similar between groups ([ t s] <1.16, p s>0.25), therefore suggesting that noise did not differentially bias amplitude measurement for either group [43].…”
Section: Resultsmentioning
confidence: 89%
“…Given the small amplitude of the N2b response, six centro-frontal channels (FC1, FC2, FCz, C1, C2, and Cz) were grouped in our analysis. For each subject, mean amplitude values in the selected time windows for the ERP components were calculated for the deviant-to-standard difference waveforms under the four conditions (i.e., two spectral contrasts by two attentional conditions) (Luck, 2005; Clayson et al, 2013). …”
Section: Methodsmentioning
confidence: 99%